Method of separation and collection from laminate

A two-step method using basic compounds to separate printing and adhesive layers from plastic packaging materials addresses the inefficiencies in existing recycling methods, achieving high-quality recycled materials with reduced re-attachment.

JP2025016824AActive Publication Date: 2025-02-05TOYO INK MFG CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023119540
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05
Estimated Expiration
2043-07-24

AI Technical Summary

Technical Problem

Existing methods for recycling multi-layered plastic packaging materials face challenges in efficiently separating and removing printing and adhesive layers from plastic base materials, leading to reduced quality and re-attachment issues, which affect the recycling process and the properties of the recovered materials.

Method used

A method involving a two-step process using basic compounds in solutions to swell and separate the printing and adhesive layers from plastic base materials, including immersion and stirring steps to enhance separation efficiency and reduce re-attachment.

Benefits of technology

The method effectively removes a significant portion of the printing and adhesive layers, resulting in high-quality recycled plastic base materials with minimal re-attachment, improving the recycling process and the quality of recycled products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016824000001
    Figure 2025016824000001
  • Figure 2025016824000002
    Figure 2025016824000002
Patent Text Reader

Abstract

To provide: an efficient method of separation and collection from a laminate suitable for plastic recycling, the method allowing excellent detachment of a printed layer, an adhesive layer and the like from a plastic substrate while inhibiting reattachment of detached components from detachable layers to the plastic substrate; a manufacturing method of a molding material obtained by melt-kneading the collected plastic substrate; and a manufacturing method of a high-quality molded product obtained by heating and molding the molding material.SOLUTION: The invention provides a laminate separation and collection method for separating and collecting a first substrate from a laminate, which includes at least the first substrate and a first detachable layer in contact with the first substrate. The method includes the following steps: a step 1 of leaving the laminate immersed in a first detachment liquid containing a basic compound for a predetermined period; and a step 2 of stirring the laminate, which has undergone the step 1, in a second detachment liquid containing a basic compound so as to detach the detachable layer, thereby collecting the first substrate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] An embodiment of the present invention relates to a method for separating and recovering a substrate from a laminate including at least a first substrate and a release layer in contact with the first substrate. Another embodiment of the present invention relates to a method for producing a molding material from the separated and recovered substrate and a method for producing a molded product. [Background technology]

[0002] In recent years, packaging, plastic bottles, and other plastic products made from plastic film have been discarded or dumped as garbage in the ocean, causing environmental pollution. These plastic products break down in seawater and become submicron-sized fragments (microplastics), which float in the seawater. These microplastics are ingested by marine organisms such as fish and become concentrated in their bodies, raising concerns that they may affect the health of seabirds and humans who consume these marine organisms as food.

[0003] The plastic products include food packaging packages having a multi-layer structure using plastic films, and various plastic substrates such as polyester substrates, nylon substrates (NY), polypropylene substrates (PP), and polyethylene substrates (PE) are used as film substrates in such food packaging packages. These film substrates are printed with printing ink, bonded to other film substrates or heat-melting resin substrates via adhesives, and then cut and heat-sealed to form packages. However, such food packaging packages having a multi-layer structure contain multiple incompatible materials, and therefore have the problem that they cannot be recycled as they are.

[0004] Regarding material recycling of such multi-layered packaging materials, for example, Patent Document 1 discloses a technology for removing printed layers not only from surface-printed laminates but also from multi-layered laminates by treating a laminate having a removal layer containing a polyurethane resin having a predetermined acid value with an alkaline aqueous solution. Patent Document 2 discloses a technique for removing an adhesive layer from a laminate having a multi-layer structure by treating the laminate including a polyester polyol-based adhesive having a predetermined acid value with an alkaline aqueous solution. However, in the detachment process described in Patent Documents 1 and 2, if the amount of packaging material treated with the alkaline aqueous solution is increased in order to improve productivity, the detachment property decreases, and further, the printed layer and adhesive layer separated from the plastic substrate are finely dispersed and reattached to the separated plastic substrate, which causes problems. Furthermore, molding materials obtained by recycling such substrates suffer from poor appearance and poor physical properties due to coloration.

[0005] Furthermore, Patent Document 3 discloses a technique in which a shrink label having an alkali-releasable ink layer is immersed in an alkali and then immersed in water while being agitated, thereby removing the ink layer from the shrink label. However, the technology described in Patent Document 3 uses a special substrate called a shrink label, and it is difficult to remove the printed layer and adhesive layer from a multi-layer laminate using a general-purpose substrate by repurposing the technology. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2020-090627 A [Patent Document 2] JP 2020-084130 A [Patent Document 3] International Publication No. 2021 / 225070 Summary of the Invention [Problem to be solved by the invention]

[0007] Therefore, the object of the present invention is to provide an efficient separation and recovery method for a laminate suitable for plastic recycling, which has excellent detachability of a printed layer or an adhesive layer from a plastic substrate, and further suppresses reattachment of components detached from the detachment layer to the plastic substrate. Further, the object of the present invention is to provide a method for producing a molding material obtained by melt-kneading the recovered plastic substrate, and a method for producing a high-quality molded product obtained by hot-molding the molding material. [Means for solving the problem]

[0008] As a result of thorough investigation, the inventors have found that the problem can be solved by the following method. That is, the present invention provides The present invention relates to a method for separating and recovering a laminate, which separates and recovers a first substrate from a laminate comprising at least a first substrate and a first detachment layer in contact with the first substrate, and includes the following steps 1 and 2: (Step 1) A step of leaving the laminate in a state of being immersed in a first release solution containing a basic compound for a certain period of time. (Step 2) This relates to a step of agitating the laminate that has been subjected to step 1 in a second release liquid containing a basic compound to release the release layer, thereby recovering the first base material.

[0009] The present invention also relates to the above separation and recovery method, wherein the first substrate is a polyolefin substrate.

[0010] The present invention also relates to any of the above separation and recovery methods, wherein the laminate further comprises a second substrate.

[0011] The present invention also relates to the above separation and recovery method, wherein the laminate further comprises a second detachment layer in contact with the second substrate.

[0012] The present invention also relates to any of the above separation and recovery methods, wherein the laminate further comprises a two-component curing adhesive layer containing a polyol component and a polyisocyanate component.

[0013] The present invention also relates to any one of the above separation and recovery methods, wherein the laminate is a package.

[0014] The present invention also relates to any of the above separation and recovery methods, wherein the first elution liquid and / or the second elution liquid contains water and a surfactant.

[0015] The present invention also relates to any one of the above separation and recovery methods, wherein the time required for step 2 is 1:1 or less relative to the time required for step 1.

[0016] The present invention also relates to a method for producing a molding material, which comprises melt-kneading the base material 1 separated and recovered by any one of the above-mentioned separation and recovery methods.

[0017] The present invention also relates to a method for producing a molded article, which comprises hot molding the molding material produced by the above-mentioned production method. Effect of the Invention

[0018] According to the present invention, it is possible to provide an efficient separation and recovery method for a laminate suitable for plastic recycling, which has excellent detachability of a printed layer or an adhesive layer from a plastic substrate, and further suppresses reattachment of components detached from the detachment layer to the plastic substrate. Furthermore, it is possible to provide a method for producing a molding material obtained by melt-kneading the recovered plastic substrate, and a method for producing a high-quality molded body obtained by hot-molding the molding material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The following describes in detail the embodiments of the present invention. However, the following description of the embodiments or requirements is merely an example of the embodiments of the present invention, and the present invention is not limited to these contents as long as it does not deviate from the gist of the present invention.

[0020] <Separation and recovery method> The method for separating and recovering a laminate according to an embodiment of the present invention is characterized by including step 1 of immersing a laminate comprising at least a first substrate and a first detachment layer in contact with the first substrate in a first detachment liquid containing a basic compound and leaving it in that state for a certain period of time, and step 2 of agitating the laminate in a second detachment liquid containing a basic compound to remove the first detachment layer and recover the first substrate.

[0021] In the embodiment of the present invention, unless otherwise specified, "detachment" and "separation" refer to a part or all of a series of behaviors in which a substrate and a layer in contact with the substrate change from a contact state to a non-contact state due to the presence of a release liquid, and are synonymous. It is presumed that detachment occurs due to the action between a component added to the release liquid and a site in the release layer that has affinity for the added component. In addition, when there are two or more release layers, detachment may occur simultaneously at each location. For example, this refers to the case where the release layer dissolves or swells in the release liquid and peels off, causing the substrate to detach from the laminate, and includes one or both of the following cases: (1) the release layer dissolves and the substrate is detached, and (2) even if the release layer does not dissolve, it peels off due to neutralization or swelling, etc., and the substrate is detached.

[0022] In the separation and recovery method, in step 1, the laminate is immersed in a first elution liquid containing a basic compound in a elution treatment vessel for a certain period of time, thereby causing the elution layer on the substrate to swell and decreasing the adhesion to the substrate. In addition, since no stirring is required, it is possible to charge a large amount of elution liquid in the vessel and also to increase the amount of the laminate relative to the elution liquid, thereby significantly improving productivity. Furthermore, in step 2, by stirring the laminate in a second release liquid containing a basic compound, it is possible to remove the release layer and recover the first base material even in the case of a laminate having a multi-layer structure. In the present invention, by combining step 1 and step 2, the detached base material having good detachability and reattachability can be efficiently recovered, and a high-quality recycled material can be produced.

[0023] Since the present invention aims to obtain the plastic substrate after the detachment as a recycled substrate or a regenerated substrate, an embodiment in which the detachment layer and the like are removed from the plastic substrate as much as possible is preferable. Specifically, it is preferable that at least 50% by mass or more of the detachment layer is detached in the area or thickness direction out of 100% by mass of the detachment layer. More preferably, it is preferable that 60% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more is detached.

[0024] <Removal solution> In the present invention, the first release liquid used in step 1 and the second release liquid used in step 2 each contain a basic compound. By containing a basic compound, the release layer can be swelled and released. The elution liquid preferably contains water in an amount of 50% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. The first and second desorption liquids may have either the same composition or different compositions.

[0025] The release liquid penetrates the end of the laminate, contacts the release layer, and dissolves or swells to separate the plastic substrate from the release layer. Therefore, in order to efficiently proceed with the release step, it is preferable that the laminate is cut or crushed and the release layer is exposed on the cross section when immersed in the release liquid. In such a case, the substrate can be released in a shorter time.

[0026] [Basic compounds] In an embodiment of the present invention, the release liquid is a basic aqueous solution containing a basic compound. The basic compound is not particularly limited, and for example, sodium hydroxide (NaOH), potassium hydroxide (KOH), calcium hydroxide (Ca(OH)2), ammonia, barium hydroxide (Ba(OH)2), and sodium carbonate (Na2CO3) are preferably used. More preferably, it is at least one selected from the group consisting of sodium hydroxide and potassium hydroxide. The content of the basic compound in the basic aqueous solution is preferably in the range of 0.5 to 20 mass%, more preferably 1 to 15 mass%, and further preferably 2 to 15 mass%, based on the mass of the basic aqueous solution. Within the above range, the basic aqueous solution can retain sufficient basicity to remove the detachment layer described below by dissolving or swelling, and recover the plastic substrate.

[0027] [Surfactants] The desorption liquid may contain a surfactant. The surfactant mainly plays a role in improving the releasability of the release layer. This is thought to be because the action of the surfactant makes it easier for the release liquid to penetrate into the release layer of the primer layer, the printing layer, the adhesive layer, etc., and promotes the release. In addition, the surfactant is thought to adsorb to the released components and the surface of the substrate, thereby preventing the reattachment of finely dispersed printing layers, etc. In addition, when the amount of the laminate relative to the release liquid is increased during separation and recovery, particularly when the plastic substrate is an olefin substrate, the laminate and the separated substrate tend to curl with the released ink particles wrapped around them, and even if the substrate is immersed in the release liquid, it is difficult to completely remove the ink particles and other particles wrapped around the curl. However, when the release liquid contains a surfactant, curling is suppressed. As a result, release properties are improved and reattachment can be suppressed. This is thought to be due to the surfactant being adsorbed onto the surfaces of the laminate and the separated substrate.

[0028] The HLB value of the surfactant in the embodiment of the present invention is preferably 7 or more. With an HLB value of 7 or more, excellent releasability and anti-reattachment properties are exhibited as described above. The HLB value of the surfactant is preferably 8 or more, more preferably 10 or more. The HLB value of the surfactant is preferably 20 or less, more preferably 19 or less, and even more preferably 17 or less. An HLB value of 20 or less is preferable because it has excellent defoaming properties.

[0029] The HLB value is an index value relating to the affinity of a surfactant for water and oil, and is divided equally between an HLB value of 0 for a substance having no hydrophilic groups and an HLB value of 20 for a substance having only hydrophilic groups. The concept of HLB was proposed by William Griffin of the Atlas Powder Company in 1949, and several methods for determining HLB by calculation have been proposed, but in the embodiment of the present invention, the HLB value can be calculated from the following formula using the Griffin method. Formula) HLB = 20 x [(molecular weight of hydrophilic group contained in surfactant) / (molecular weight of surfactant)] Examples of the hydrophilic group contained in the surfactant include a hydroxyl group and an ethyleneoxy group.

[0030] The type of surfactant may be, for example, nonionic, anionic, cationic, or amphoteric, and the type and amount of the surfactant may be appropriately selected according to the required properties. From the viewpoint of releasing property and foaming property, the surfactant is preferably at least one selected from the group consisting of anionic surfactants and nonionic surfactants. Moreover, the surfactant preferably has a structure with an alkylene oxide (hereinafter, also referred to as AO) added thereto, since this improves the releasing property and the preventing property of reattachment.

[0031] (Nonionic surfactant) The nonionic surfactant is not particularly limited, but is preferably an alkylene oxide adduct in which an alkylene oxide is added. More preferably, it is a compound obtained by adding an alkylene oxide to an alcohol having active hydrogen, a compound obtained by adding an alkylene oxide to an amine, or a compound obtained by adding an alkylene oxide to a fatty acid. The above addition may be either random addition or block addition. In addition, the number of carbon atoms of the alkylene oxide is preferably 2 to 4. The nonionic surfactant is more preferably an alcohol-based nonionic surfactant in which an alkylene oxide having 2 to 4 carbon atoms is added to an alcohol.

[0032] [Alcohol-based nonionic surfactant] Examples of the alcohol-based nonionic surfactant include alkylene oxide adducts of primary or secondary alcohols having a total of 8 to 24 carbon atoms, and alkylene oxide adducts of alkylphenols having a total of 8 to 12 carbon atoms. The primary or secondary alcohols having a total of 8 to 24 carbon atoms may be either saturated or unsaturated. Examples of the primary or secondary alcohol having a total of 8 to 24 carbon atoms include lauryl alcohol, stearyl alcohol, oleyl alcohol, dodecyl alcohol, arachidyl alcohol, behenyl alcohol, lignoceryl alcohol, and myristyl alcohol. Examples of the alkylene oxide added to the alcohol include ethylene oxide, propylene oxide, and butylene oxide, and it is preferable to use ethylene oxide as an essential component. The number of moles of the alkylene oxide added is preferably 1 to 100 moles, more preferably 2 to 50 moles, per mole of the alcohol or alkylphenol. The above range is preferable because it has excellent elimination properties.

[0033] [Fatty acid-based nonionic surfactant] The structure of the fatty acid-based nonionic surfactant is not particularly limited, and examples thereof include alkylene oxide adducts of higher fatty acids having a total of 10 to 24 carbon atoms, fats and oils consisting of esters of the above-mentioned saturated or unsaturated higher fatty acids having a total of 10 to 24 carbon atoms and glycerin, and further, alkylene oxide adducts of mixtures of the above-mentioned fats and oils and polyhydric alcohols having 2 to 10 carbon atoms. The above-mentioned higher fatty acids having a total of 10 to 24 carbon atoms may be either saturated or unsaturated. Examples of the higher fatty acid having a total carbon number of 10 to 24 include saturated higher fatty acids such as lauric acid, myristic acid, palmitic acid, stearic acid, arachic acid, and behenic acid; and unsaturated higher fatty acids such as palmitoleic acid, oleic acid, elaidic acid, linoleic acid, linolenic acid, erucic acid, and ricinoleic acid. Examples of the dihydric to decahydric polyhydric alcohol include ethylene glycol, propylene glycol, glycerin, polyglycerin, sorbitol, sorbitan, and sucrose. The type and molar number of the alkylene oxide are the same as those described in the above section on [Alcohol-based nonionic surfactants].

[0034] [Amine-based nonionic surfactant] Examples of the amine-based nonionic surfactant include AO adducts of saturated or unsaturated primary or secondary amines having a total carbon number of 8 to 36. Examples of the amine include 2-ethylhexylamine, di-2-ethylhexylamine, laurylamine, dilaurylamine, tetradecylamine, ditetradecylamine, hexadecylamine, dihexadecylamine, stearylamine, distearylamine, oleylamine, dioleylamine, etc. The type and number of moles of AO added are the same as above.

[0035] (anionic surfactant) The anionic surfactant is preferably a non-soap surfactant, and examples thereof include sulfonic acid-based anionic surfactants, sulfate ester-based anionic surfactants, carboxylate-based anionic surfactants, and phosphate ester-based anionic surfactants.

[0036] [Sulfonic acid-based anionic surfactant] Examples of the sulfonic acid anionic surfactant include alkylsulfonic acid, alkylbenzenesulfonic acid, alkylnaphthalenesulfonic acid, alkyldiphenyletherdisulfonic acid, alkylmethyltaurine, sulfosuccinic acid diester, alkylene oxide adduct of sulfonic acid, and their salts.Specific examples include hexanesulfonic acid, octanesulfonic acid, decanesulfonic acid, dodecanesulfonic acid, toluenesulfonic acid, cumenesulfonic acid, octylbenzenesulfonic acid, dodecylbenzenesulfonic acid, dinitrobenzenesulfonic acid, and lauryldodecylphenyletherdisulfonic acid.

[0037] [Sulfate ester-based anionic surfactants] Examples of the sulfate anionic surfactant include sulfate (alkyl ether sulfate), alkylene oxide adduct of sulfate, and salts thereof. Specific examples include lauryl sulfate, myristyl sulfate, and polyoxyethylene lauryl ether sulfate.

[0038] [Carboxylic acid type anionic surfactant] Examples of the carboxylic acid-based anionic surfactant include alkyl carboxylic acids, alkyl benzene carboxylic acids, alkylene oxide adducts of carboxylic acids, and salts thereof.Specific examples of the surfactant that can be used include lauric acid, myristic acid, palmitic acid, stearic acid, polyoxyethylene lauryl ether acetic acid, and polyoxyethylene tridecyl ether acetic acid.

[0039] [Phosphate-based anionic surfactant] Examples of the phosphate anionic surfactant include phosphate (alkyl ether phosphate), alkylene oxide adduct of phosphate, and salts thereof.Specific examples include octyl phosphate, lauryl phosphate, tridecyl phosphate, myristyl phosphate, cetyl phosphate, stearyl phosphate, polyoxyethylene octyl ether phosphate, polyoxyethylene lauryl ether phosphate, etc.

[0040] The anionic surfactant preferably has an alkyl group having 2 to 24 carbon atoms or an alkenyl group having 2 to 24 carbon atoms, and more preferably has an alkyl group having 8 to 18 carbon atoms. The alkyl group or the alkenyl group may be linear or branched. In addition, when the anionic surfactant is an alkylene oxide adduct, the alkylene oxide may be, for example, ethylene oxide, propylene oxide, or butylene oxide, with ethylene oxide being preferred. The number of moles of alkylene oxide added is preferably 1 to 12 moles, more preferably 1 to 8 moles, per mole of alcohol or alkylphenol. The above range is particularly preferred because of excellent releasability.

[0041] Examples of the salt constituting the anionic surfactant include metal salts such as sodium, potassium, magnesium, calcium, etc. These salts may be used alone or in combination of two or more. Among these, from the viewpoint of releasability and anti-reattachment properties, preferred anionic surfactants are sulfonate type and phosphate type, and more preferred are alkyl sulfonate, polyoxyalkylene alkyl ether sulfonate, polyoxyalkylene alkyl ether phosphate, etc.

[0042] (Cationic Surfactant) Examples of cationic surfactants include alkylamine salts and quaternary ammonium salts.Specific examples of usable surfactants include stearylamine acetate, trimethyl coconut ammonium chloride, trimethyl beef tallow ammonium chloride, dimethyldioleyl ammonium chloride, methyl oleyl diethanol chloride, tetramethyl ammonium chloride, lauryl pyridinium chloride, lauryl pyridinium bromide, lauryl pyridinium disulfate, cetyl pyridinium bromide, 4-alkyl mercaptopyridine, poly(vinylpyridine)-dodecyl bromide, and dodecyl benzyl triethyl ammonium chloride.

[0043] (Amphoteric surfactant) Examples of amphoteric surfactants include lauryl dimethylaminoacetate betaine, 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine, coconut oil fatty acid amidopropyl dimethylaminoacetate betaine, polyoctyl polyaminoethyl glycine, and imidazoline derivatives.

[0044] These surfactants may be used alone or in combination of two or more. The content of the surfactant in the release liquid is preferably in the range of 0.001 to 10 mass%, more preferably in the range of 0.005 to 7 mass%, further preferably in the range of 0.03 to 5 mass%, and still more preferably in the range of 0.05 to 3 mass%, based on the mass of the release liquid. A content of 0.001 mass% or more is preferable because of excellent release properties and anti-reattachment properties, and a content of 10 mass% or less is preferable from the viewpoint of defoaming properties.

[0045] [Antifoaming agent] In an embodiment of the present invention, the release liquid further contains an antifoaming agent in combination with the above-mentioned surfactant, thereby exhibiting good antifoaming properties without reducing the release property and the anti-reattachment property, and making it possible to suppress foaming caused by the surfactant. Examples of the antifoaming agent include silicone-based compounds and non-silicone-based compounds.

[0046] (Silicone compounds) Examples of the silicone-based compound include emulsion type, self-emulsifying type, oil type, oil compound type, and solvent type. The emulsion type is a silicone-based defoamer in which a silicone oil compound is emulsified with an activator to form an O / W type (oil in water type) emulsion. Examples of such antifoamers include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., "FC2913" and "SILFOAMSE47" manufactured by Asahi Kasei Wacker Silicone Co., Ltd., and "BYK-015" and "BYK-1640" manufactured by BYK Japan. The self-emulsifying type is a silicone-based defoamer that is 100% active ingredient and becomes an emulsion when diluted and mixed with water. Examples include "KS-540" and "X-50-1176" manufactured by Shin-Etsu Chemical Co., Ltd., and "SILFOAM SD670" and "SILFOAM SD850" manufactured by Wacker Asahi Kasei Silicones. Oil-type defoamers are 100% silicone oil defoamers that do not contain solvents or additives. Examples include "KM-89" and "KM-98" made by Shin-Etsu Chemical Co., Ltd., "AK350" and "AK12500" made by Asahi Kasei Wacker Silicone, and "BYK-1770" made by BYK Japan. Oil compound type is a silicone-based defoamer that combines silica particles with silicone oil. Examples include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., "SILFOAM SC370" and "PULPSIL22274VP" manufactured by Asahi Kasei Wacker Silicone, and "BYK-017" and "BYK-018" manufactured by BYK Japan. Solvent-type defoamers are silicone-based defoamers in which silicone oil is dissolved in a solvent. Examples include "KM-89" and "KM-98" manufactured by Shin-Etsu Chemical Co., Ltd., and "BYK-019" and "BYK-025" manufactured by BYK Japan.

[0047] (Non-silicone compounds) Examples of the non-silicone compounds include fatty acid ester compounds, urea resin compounds, paraffin compounds, polyoxyalkylene glycol compounds, acrylic ester copolymers, ester polymers, ether polymers, amide polymers, emulsion types of mineral oils, polysiloxane adducts, fluorine compounds, vinyl polymers, acetylene alcohol, acrylic polymers, special vinyl polymers, ethylene glycol, and higher alcohols (such as octyl alcohol and cyclohexanol).

[0048] The defoaming agent may be used alone or in combination of two or more. The content of the defoaming agent in the release liquid is preferably in the range of 0.0001 to 5 mass%, more preferably in the range of 0.001 to 4.5 mass%, further preferably in the range of 0.01 to 4 mass%, still more preferably in the range of 0.02 to 3.5 mass%, and particularly preferably in the range of 0.03 to 3 mass%, based on the mass of the release liquid. When it is 0.0001 mass% or more, the defoaming property is excellent, and when it is 5 mass% or less, the release property and the anti-reattachment property are excellent.

[0049] The above-mentioned defoaming agent is preferably at least one selected from the group consisting of emulsion-type silicone compounds, self-emulsifying silicone compounds, and non-silicone compounds, from the viewpoints that it has good alkali resistance and is unlikely to deteriorate releasability or anti-reattachment properties when combined with the above-mentioned surfactant.

[0050] <Process 1, Process 2> The separation and recovery method of the present invention is characterized by having the following two steps, step 1 and step 2. (Step 1) A step of leaving the laminate in a state of being immersed in a first release solution containing a basic compound for a certain period of time. (Step 2) A step of agitating the laminate that has been subjected to step 1 in a second release liquid containing a basic compound to release the release layer, and recovering the first base material. In step 1, the laminate is put into the first release liquid, immersed, and left to stand for a certain period of time. The term "standing" here means that the laminate is not subjected to a physical external stimulus to the extent that the release layer is released from the substrate. In other words, even without a physical external stimulus, the release layer may be released or dissolved. Even without a physical external stimulus, most of the released layer components are released while maintaining the shape of the layer. In addition, most of the released layer components that have not been released are in a state where they will be released if there is a slight external stimulus. Therefore, by having this step, the release layer is not crushed excessively, making it easier to remove the release layer after release. In step 2, stirring, which is an external physical stimulus, is carried out in order to promote detachment of the detached layer.

[0051] The temperature of the elution liquid in steps 1 and 2 is preferably in the range of 25 to 120°C, more preferably 30 to 120°C, and particularly preferably 30 to 80°C. In contrast to step 2, which involves stirring, in step 1, it is sufficient that the laminate is immersed in the release liquid, so the volume ratio of the release liquid to the kettle and the mass ratio of the laminate to the release liquid can be set larger in step 1. The volume ratio of the release liquid to the kettle in step 1 is preferably 10% to 100%, more preferably 20% to 90%, and even more preferably 30% to 80%. The volume ratio of the release liquid to the kettle in step 2 is preferably 10% to 80%, more preferably 20% to 70%, and even more preferably 30% to 60%. The mass ratio of the laminate to the release liquid in step 1 is preferably 10% to 50%, more preferably 14% to 40%, and even more preferably 18% to 30%. The mass ratio of the laminate to the release liquid in step 2 is preferably 0.5 to 10%, more preferably 1 to 8%, and even more preferably 2 to 6%. The time for leaving the mixture in the elution liquid in step 1 is preferably 1 minute to 12 hours, more preferably 5 minutes to 6 hours, even more preferably 10 minutes to 3 hours, and particularly preferably 30 minutes to 2 hours. The time for stirring in the elution liquid in step 2 is preferably 1 minute to 5 hours, more preferably 2 minutes to 4 hours, even more preferably 5 minutes to 2 hours, and particularly preferably 8 minutes to 45 minutes. Considering productivity and re-adhesion of the printed layer after detachment, it is preferable that the time required for step 1 is longer than that for step 2. With respect to the time required for step 1 being 1, the time required for step 2 is preferably 1 or less, more preferably 0.1 to 1.0, even more preferably 0.1 to 0.5, and particularly preferably in the range of 0.15 to 0.4. In step 1, particularly immediately after the addition, the laminate is immersed as uniformly as possible in the release liquid, and may be stirred very gently so that the release layer does not come off from the substrate, which includes the case of being left still. The stirring speed in step 2 is preferably 80 to 5000 rpm, more preferably 100 to 4000 rpm.

[0052] The detachment layer is detached from the laminate, and the plastic substrate is recovered, and the plastic substrate is washed with water and dried to obtain a recycled substrate. The removal rate of the detachment layer on the surface of the substrate is preferably 70% or more, more preferably 80% or more, and particularly preferably 90% or more, based on the area of ​​the detachment layer before detachment. The resulting recycled base material can be processed into pellets using an extruder or the like and reused as recycled resin.

[0053] Step 1 and step 2 may be steps carried out in the same vessel or in different vessels. The second elution liquid may be the first elution liquid used as is, or may be the first elution liquid whose amounts of components contained in the first elution liquid have been changed, or may be a completely replaced liquid (when completely replaced, it may have the same composition ratio as the first elution liquid). In step 2, the components such as the release liquid, the laminate or the released base material may be discharged once from the vessel, and then part or all of the discharged components may be circulated back to the vessel.

[0054] <Laminate> In an embodiment of the present invention, the laminate includes at least a first substrate and a first release layer in contact with the first substrate. The release layer in contact with the first substrate is released by the release liquid, so that the first substrate can be recovered and recycled.

[0055] <Detachment Layer, First Detachment Layer, Second Detachment Layer> The release layer in the embodiment of the present invention is a layer that can be released from the substrate by a known release liquid, and is preferably a layer having a site that is compatible with the components added to the release liquid. For example, it is preferably a layer that contains a water-soluble resin or a compound having an acidic group. It is presumed that the laminate has a release layer that contains a water-soluble resin or a compound having an acidic group, so that the release liquid penetrates the release layer more easily, the release layer becomes more likely to swell, and the release of the substrate is promoted, resulting in a significantly increased release property of the printing layer and the adhesive layer. The release layer may be a cured product of a water-soluble resin or a curable compound having an acidic group, so long as it is water-soluble after curing or has an acidic group that provides an acid value. In addition, since the release layer is a layer in contact with the plastic substrate, it is preferably at least one layer selected from the group consisting of a primer layer, a printed layer, and an adhesive layer. That is, it is preferable that at least one layer selected from the group consisting of a primer layer, a printed layer, and an adhesive layer is a layer containing a water-soluble resin or a compound having an acidic group. The compound having an acidic group may be a resin or a low molecular weight compound. These water-soluble resins or compounds having an acidic group may be used alone or in combination of two or more. When there are two or more detachment layers, the components constituting each detachment layer may be the same or different.

[0056] The release layer may contain a resin component (hereinafter also referred to as a binder resin), etc. The resin component does not have to be a water-soluble resin or a compound having an acidic group. Below, the cases where the release layer is a primer layer, a printed layer, and an adhesive layer will be described respectively.

[0057] [Primer layer] When the release layer is a primer layer, the primer layer is disposed in contact with the plastic substrate, preferably has a water-soluble resin or a compound having an acidic group, and serves to release the plastic substrate by dissolution with a release liquid, peeling, or the like.

[0058] (Water-soluble resin) The water-soluble resin may be any resin that can swell or dissolve in water and be removed from the plastic substrate. The water may be heated to a temperature of about 25 to 100° C. This allows the primer layer to be removed by water (including warm water). Such resins can be selected from known resins as long as they do not impair water solubility, and examples thereof include water-soluble polyester resins, water-soluble polyamide resins, water-soluble polyimide resins, water-soluble acrylic resins, water-soluble polyurethane resins, water-soluble polyallylamine resins, water-soluble phenolic resins, water-soluble epoxy resins, water-soluble phenoxy resins, water-soluble urea resins, water-soluble melamine resins, polyvinyl alcohol resins, and modified products of these resins. These can be used alone or in combination of two or more. Among them, polyvinyl alcohol (PVA) resins are preferably used from the viewpoints of availability and release properties. When the water-soluble resin has film-forming properties, the water-soluble resin may be used as the binder resin constituting the primer layer. Examples of the water-soluble resin include a resin that is water-soluble and has an acidic group, and a resin that is water-soluble and does not have an acidic group. The water-soluble resin may be, for example, a resin that is water-soluble and does not have an acidic group.

[0059] As the polyvinyl alcohol resin, in addition to unmodified polyvinyl alcohol, modified polyvinyl alcohol obtained by copolymerizing various monomers during the production of vinyl ester resin and saponifying the copolymer, or various post-modified polyvinyl alcohols obtained by introducing various functional groups into unmodified polyvinyl alcohol by post-modification may be used. Also, modified polyvinyl alcohols further modified may be used. These modifications may be performed within a range that does not impair the water solubility of the polyvinyl alcohol resin. These resins may be used alone or in combination of two or more.

[0060] As the polyvinyl alcohol resin, a resin containing a structural unit having a primary hydroxyl group in the side chain, or an ethylene-modified polyvinyl alcohol resin is preferable. Among them, a polyvinyl alcohol resin containing a structural unit having a primary hydroxyl group in the side chain is preferable because of its excellent melt moldability and excellent water solubility. The number of primary hydroxyl groups in these structural units is usually 1 to 5, preferably 1 to 2, and more preferably 1. In addition to the primary hydroxyl groups, it is preferable to have a secondary hydroxyl group. As the polyvinyl alcohol resin containing a structural unit having a primary hydroxyl group in the side chain, for example, a modified polyvinyl alcohol resin containing a 1,2-diol structural unit in the side chain is preferable.

[0061] In an embodiment of the present invention, the saponification degree of the polyvinyl alcohol resin (measured according to JIS K 6726) is usually 60 to 100 mol%. The preferred range of the saponification degree varies depending on the modified species. For example, in the case of an unmodified polyvinyl alcohol resin, it is usually 60 to 99.9 mol%, preferably 70 to 99.0 mol%, more preferably 75 to 98.5%. The saponification degree of the modified polyvinyl alcohol resin containing a side chain 1,2-diol structural unit is usually 60 to 99.9 mol%, preferably 65 to 99.8 mol%, more preferably 70 to 99.5 mol%. If the saponification degree is too low, the water solubility tends to decrease. The saponification degree of the ethylene-modified polyvinyl alcohol resin modified with a small amount of ethylene is usually 60 mol% or more, preferably 70 to 99.5 mol%, particularly preferably 75 to 99.0 mol%. The saponification degree within the above range is preferable because it provides excellent water solubility and good releasability, and is also preferable because it provides excellent coatability when forming a primer layer.

[0062] The average degree of polymerization of the polyvinyl alcohol resin (measured in accordance with JIS K 6726) is usually 100-3,000, preferably 150-2,000, more preferably 180-1,000, and particularly preferably 200-800.

[0063] (Compounds having an acidic group) The compound having an acidic group may be a resin having an acidic group or a low molecular weight compound having an acidic group. This allows the primer layer to be detached by the above-mentioned basic aqueous solution. Examples of the resin having an acidic group include a water-soluble resin having an acidic group and a water-insoluble resin having an acidic group. The resin having an acidic group may be, for example, a water-soluble resin or an insoluble resin as long as it has an acidic group.

[0064] Examples of the resin that is the main chain of the resin having an acidic group include cellulose resin, urethane resin, polyamide resin, vinyl chloride / vinyl acetate copolymer, ketone resin, polyester resin, and (meth)acrylic resin. These resins can be polymerized using a raw material having an acidic group, or can be reacted with a compound having an acidic group after polymerization to form a resin having an acidic group. Examples of the acidic group include a carboxy group, a phosphoric acid group, a sulfo group, a sulfino group, or the like, or an ester or salt thereof. Furthermore, as the resin having an acidic group, a rosin-modified resin having an acid value, such as maleic rosin or fumaric rosin, can be used. In addition, examples of resins having an acidic group that can be used include radical copolymers such as styrene-(meth)acrylic resins, styrene-maleic acid (anhydride) resins, and terpene-maleic acid (anhydride) resins, which are copolymerized with polymerizable monomers having an acidic group, such as polymerizable monomers having a carboxy group, such as itaconic acid, maleic acid, fumaric acid, and cinnamic acid; polymerizable monomers which are acid anhydrides, such as itaconic acid anhydride and maleic acid anhydride; polymerizable monomers having a sulfonic acid group, such as sulfonated styrene; and polymerizable monomers having a sulfonamide group, such as vinylbenzenesulfonamide; and acid-modified polyolefin resins. These may be used alone or in combination of two or more.

[0065] The low molecular weight compound having an acidic group refers to a compound that does not have a molecular weight distribution and has a molecular weight of 1,000 or less. Examples of such compounds include saturated fatty acids such as lauric acid, myristic acid, palmitic acid, margaric acid, and stearic acid; unsaturated fatty acids such as oleic acid, linoleic acid, linolenic acid, arachidonic acid, eicosapentaenoic acid, docosahexaenoic acid, and sorbic acid; hydroxy acids such as lactic acid, malic acid, and citric acid; aromatic carboxylic acids such as benzoic acid, phthalic acid, isophthalic acid, terephthalic acid, salicylic acid, gallic acid, mellitic acid, and cinnamic acid; dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, and maleic acid; tricarboxylic acids such as aconitic acid; oxocarboxylic acids such as pyruvic acid and oxaloacetic acid; carboxylic acid derivatives such as amino acids and nitrocarboxylic acids; and acid anhydrides such as trimellitic anhydride and pyromellitic anhydride. The low molecular weight compound having an acidic group can be used in combination with the above-mentioned resin having an acidic group or a known binder resin constituting a known primer layer to form a primer layer.

[0066] From the viewpoint of recoating suitability, the primer layer preferably contains a compound having an acidic group. Also, from the viewpoint of printability, the primer layer preferably contains a urethane resin having an acidic group, an acrylic resin having an acidic group, or a rosin-modified resin. The primer layer may contain one of these resins alone or two or more of them in combination.

[0067] [Urethane resin having acidic groups] The urethane resin having an acidic group is not particularly limited, and examples thereof include a urethane resin obtained by reacting a polyol having an acidic group with a polyisocyanate, a resin obtained by acid-modifying hydroxyl groups in a urethane resin obtained by reacting a polyol with a polyisocyanate, and a resin obtained by acid-modifying amino groups in a urethane urea resin obtained by reacting a polyamine with an isocyanate group in a urethane resin obtained by reacting a polyol with a polyisocyanate. Furthermore, by using a polyol having an acidic group as the polyol, it is possible to impart an acid value derived from the carboxy group to the urethane resin, and it is possible to improve the releasability.

[0068] Polyol Polyol is a general term for a compound having at least two hydroxyl groups in one molecule. The number average molecular weight of the polyol is preferably 500 to 10,000, more preferably 1,000 to 5,000. The number average molecular weight is calculated from the hydroxyl value of the polyol, and the hydroxyl value refers to a value measured according to JIS K 0070. When the number average molecular weight of the polyol is 500 or more, the flexibility of the primer layer is excellent and the adhesion to the plastic substrate is improved. When the number average molecular weight is 10,000 or less, the blocking resistance to the plastic substrate is excellent.

[0069] The polyol is not particularly limited, and more preferably, at least one polyol selected from the group consisting of polyester polyol, polyether polyol, and polycarbonate polyol is used. The polyol may further include other dimer diol, hydrogenated dimer diol, castor oil modified polyol, etc. That is, the urethane resin preferably contains a structural unit derived from at least one polyol selected from the group consisting of polyester polyol, polyether polyol, and polycarbonate polyol. Since the ester bond site of the polyester polyol is hydrolyzed by alkali to improve the releasability, the urethane resin more preferably contains a structural unit derived from a polyester polyol. The content of the structural units derived from polyol is preferably 10 to 75% by mass, more preferably 15 to 70% by mass, and even more preferably 20 to 65% by mass, based on the total amount of the urethane resin. The content of the structural units derived from polyester polyol is preferably 5% by mass or more, more preferably 30% by mass or more, even more preferably 60% by mass or more, and particularly preferably 80% by mass or more, based on the total amount of the structural units derived from polyol.

[0070] Hydroxy acids The polyol may contain a hydroxy acid. The hydroxy acid refers to a compound having both a hydroxyl group, which is an active hydrogen group, and an acidic functional group in one molecule. The acidic functional group refers to a functional group that can be neutralized with potassium hydroxide when measuring the acid value, and specifically includes a carboxy group and a sulfonic acid group, and is preferably a carboxy group. As such a hydroxy acid, for example, dimethylolalkanoic acid such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, and 2,2-dimethylolvaleric acid is preferably used.

[0071] <Polyisocyanate> The polyisocyanate is not particularly limited and can be selected from conventionally known polyisocyanates. It preferably contains a diisocyanate or triisocyanate, and more preferably contains an aromatic, aliphatic or alicyclic diisocyanate. These may be used alone or in combination of two or more kinds.

[0072] Polyamines The polyamine for forming the urethane urea is not particularly limited, and is preferably a diamine compound. A diamine having a hydroxyl group may be used because it can introduce a hydroxyl group into the urethane resin.

[0073] The acid value of the urethane resin having an acidic group is preferably 15 mgKOH / g or more, more preferably 15 to 70 mgKOH / g, and even more preferably 20 to 50 mgKOH / g. If it is 15 mgKOH / g or more, the release property by the release liquid is improved, and if it is 70 mgKOH / g or less, the adhesion to the substrate and the retort resistance are improved, which are preferable. The hydroxyl value of the urethane resin is preferably 1 to 35 mgKOH / g, more preferably 10 to 30 mgKOH / g. If it is 1 mgKOH / g or more, the releasability by the release solution is improved, and if it is 35 mgKOH / g or less, the adhesion to the substrate is improved, which is preferable.

[0074] The weight average molecular weight of the urethane resin having an acidic group is preferably 10,000 to 100,000, more preferably 15,000 to 70,000, and even more preferably 15,000 to 50,000. The molecular weight distribution (Mw / Mn) of the urethane resin is preferably 6 or less. Mw represents the weight average molecular weight, and Mn represents the number average molecular weight. When the molecular weight distribution is 6 or less, the release property, drying property of the primer composition, and retort resistance are excellent. In addition, the smaller the molecular weight distribution, that is, the sharper the molecular weight distribution, the more uniform the dissolution or peeling action by the release liquid occurs, and the more the release property of the plastic substrate is improved. The molecular weight distribution is more preferably 5 or less, and even more preferably 4 or less. In addition, the molecular weight distribution is preferably 1.5 or more, and more preferably 1.2 or more. In this specification, Mw, Mn and molecular weight distribution (Mw / Mn) are polystyrene equivalent values ​​determined by gel permeation chromatography (GPC).

[0075] The urethane resin having an acidic group may have an amine value. When the urethane resin has an amine value, the amine value is preferably 0.1 to 20 mgKOH / g, and more preferably 1 to 10 mgKOH / g. When the amine value is within the above range, the adhesion to the substrate is excellent.

[0076] The number of urethane bonds in the polyurethane resin having an acidic group is preferably 1 to 3 mmol / g, more preferably 1.5 to 2 mmol / g. The number of urea bonds is preferably 0 to 3 mmol / g, more preferably 0.2 to 1 mmol / g. The total number of urethane bonds and urea bonds is preferably 1 to 6 mmol / g, more preferably 1.7 to 3 mmol / g. By setting the number of urethane bonds and the number of urea bonds within the corresponding range, the releasability and the anti-reattachment properties are improved.

[0077] [Acrylic resin having acidic group] Examples of acrylic resins having an acidic group include polymers obtained by polymerizing a monomer containing a (meth)acrylic monomer having an acidic group, such as (meth)acrylic acid or maleic acid; and resins obtained by polymerizing a monomer containing a (meth)acrylic monomer having a hydroxyl group or a glycidyl group, and then modifying the functional group to introduce a carboxyl group (e.g., maleic anhydride modified resin). The acid value of the acrylic resin having an acidic group is preferably 50 mgKOH / g or more, and more preferably 100 mgKOH / g or more.

[0078] [Rosin-modified resin] Rosin-modified resins are resins prepared using rosin as one of the raw materials. Rosin contains a mixture of resin acids such as abietic acid, palustric acid, isopimaric acid, and levopimaric acid, and these resin acids contain hydrophilic and chemically active carboxyl groups, some of which have conjugated double bonds. For this reason, various rosin-modified resins are prepared by combining polyhydric alcohols and polybasic acids and polycondensing them, adding resol, which is a condensate of phenol, to the benzene ring contained in the rosin skeleton, or by carrying out a Diels-Alder reaction with maleic anhydride or maleic acid, which is a dienophile, to add maleic acid or maleic anhydride skeletons. Various types of such rosin-modified resins are commercially available, and it is also possible to obtain and use them.

[0079] Examples of rosin-modified resins include maleated rosin, fumarated rosin, rosin-modified maleic acid resin, rosin-modified fumaric acid resin, rosin-modified phenolic resin, rosin-modified alkyd resin, and rosin-modified polyester resin. In the embodiment of the present invention, any rosin-modified resin may be used, but among these, those containing in their structure a moiety derived from at least one selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, and fumaric anhydride are preferably used. A resin "containing in its structure a moiety derived from at least one selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, and fumaric anhydride" is one prepared using at least one selected from the group consisting of maleic acid, maleic anhydride, fumaric acid, and fumaric anhydride as part of a raw material, and means, for example, a rosin-modified maleic acid resin or rosin-modified fumaric acid resin obtained by condensation polymerization of maleic acid or fumaric acid as part of a polybasic acid, a maleated rosin or fumarated rosin having a structure in which maleic acid, maleic anhydride, fumaric acid, or fumaric anhydride is added as a dienophile by a Diels-Alder reaction, or a resin obtained by further polymerizing other chemical species using the functional groups contained in these.

[0080] The acid value of the rosin-modified resin is preferably from 10 to 400 mgKOH / g, and more preferably from 100 to 300 mgKOH / g.

[0081] (Other ingredients) The primer layer may contain a resin other than the water-soluble resin or the compound having an acidic group. Examples of such resins include cellulose resins, polyamide resins, vinyl chloride resins such as vinyl chloride-vinyl acetate copolymer resins or vinyl chloride-acrylic copolymer resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, acrylic resins, styrene resins, dammar resins, styrene-acrylic copolymer resins, polyester resins, alkyd resins, terpene resins, phenol-modified terpene resins, ketone resins, cyclized rubbers, chlorinated rubbers, butyral, polyacetal resins, petroleum resins, and modified resins thereof. These resins may be used alone or in combination of two or more. Among them, the primer layer preferably contains at least one resin selected from the group consisting of cellulose resin, vinyl chloride resin, rosin resin, and acrylic resin, and more preferably contains vinyl chloride resin or acrylic resin. The mass ratio of the urethane resin having an acidic group to the other resins (urethane resin having an acidic group:other resins) is preferably 95:5 to 50:50. When the mass ratio is within the above range, the printed layer is peeled off in a thin film state when peeled off together with the primer layer in a basic aqueous solution, which is preferable because recovery is easy.

[0082] The primer layer may contain a body pigment. Examples of the body pigment include silica, barium sulfate, kaolin, clay, calcium carbonate, magnesium carbonate, zinc oxide, zirconium oxide, and other metal oxides. Among these, silica is preferred, and hydrophilic silica is more preferred. The average particle size of the extender pigment is preferably 0.5 to 10 μm, more preferably 1 to 8 μm. The content of the extender pigment in the primer layer is preferably 0.5 to 10 mass %, more preferably 1 to 5 mass %. When the average particle size and the content of the extender pigment are within the above ranges, the wettability of the printing layer is improved, and the image quality is improved.

[0083] The primer layer may be a layer in which the above-mentioned urethane resin having an acidic group is crosslinked with a curing agent. By introducing a crosslinked structure into the primer layer, the penetration and bleeding of the printing layer formed on the primer layer is suppressed, and excellent image quality can be achieved. The curing agent may be, for example, a polyisocyanate. The polyisocyanate is not particularly limited and may be selected from conventionally known polyisocyanates, for example, an aliphatic polyisocyanate or an aromatic aliphatic polyisocyanate. These may be used alone or in combination of two or more kinds.

[0084] The primer layer may further contain known additives, such as dispersants, wetting agents, adhesion promoters, leveling agents, defoamers, antistatic agents, viscosity modifiers, metal chelates, trapping agents, antiblocking agents, wax components other than those mentioned above, and silane coupling agents.

[0085] The thickness of the primer layer is preferably in the range of 0.5 to 3.0 μm, more preferably 0.6 to 2.0 μm, and further preferably 0.8 to 1.5 μm, and can be formed by using a known method.

[0086] [Print layer] The printed layer is a layer on which any printed pattern is formed for the purpose of decoration, imparting aesthetic appeal, displaying the contents, expiration date, manufacturer or seller, etc., and includes a solid printed layer. When the release layer is a printing layer, the printing layer is disposed in contact with the plastic substrate, contains a water-soluble resin or a compound having an acidic group, and plays a role in releasing the plastic substrate by dissolving in the release liquid or peeling off. The printing layer preferably contains a water-soluble resin or a compound having an acidic group and a colorant. The method of forming the printing layer is not limited, and it can be formed using a known method. From the viewpoint of recoating suitability, the printing layer preferably contains a compound containing an acidic group. Also, from the viewpoint of printability, the printing layer preferably contains a urethane resin having an acidic group, an acrylic resin having an acidic group, or a rosin-modified resin. The printing layer may contain one of these resins alone or two or more of them in combination. For the above-mentioned water-soluble resin and compound having an acidic group, as well as the urethane resin having an acidic group, the acrylic resin having an acidic group, and the rosin-modified resin, the descriptions of (water-soluble resin), (compound having an acidic group), [urethane resin having an acidic group], [acrylic resin having an acidic group], and [rosin-modified resin] in the section [Primer layer] described above can be used.

[0087] (Coloring agent) The printing layer may be colored or colorless, and contains a known colorant used in printing inks and paints. Such colorants are not particularly limited, and may include inorganic pigments, organic pigments, dyes, metal powders that impart metallic luster, near-infrared absorbing materials, and ultraviolet absorbing materials. Examples of inorganic pigments include color pigments such as titanium oxide, red iron oxide, Prussian blue, ultramarine blue, carbon black, and graphite; and extender pigments such as calcium carbonate, kaolin, clay, barium sulfate, aluminum hydroxide, and talc. As the organic pigment, a soluble azo pigment, an insoluble azo pigment, an azo lake pigment, a condensed azo pigment, a copper phthalocyanine pigment, a condensed polycyclic pigment, etc. are suitably used. However, the pigment is not limited to these, and any pigment listed by its generic name in the Color Index can be used as appropriate. Among them, when the release solution is a basic aqueous solution, a pigment that is not eluted in the basic aqueous solution and has alkali resistance is preferred. Preventing the elution of the pigment makes it easy to reuse the basic aqueous solution. The alkali resistance of a pigment is generally estimated based on the skeleton or structure of the pigment. Examples of alkali-resistant pigments include inorganic pigments, CI Pigment Blue 15, and CI Pigment Yellow 83. When the pigment is titanium oxide, the content of titanium oxide in the printed layer is preferably 20 to 80% by mass, more preferably 30 to 75% by mass. When the pigment is an inorganic pigment other than titanium oxide, an extender pigment, or an organic pigment, the content of each of these pigments in the printed layer is preferably 0.5 to 60% by mass, more preferably 10 to 50% by mass.

[0088] (Other ingredients) The print layer may contain a pigment derivative or a resin-type dispersant as a dispersant for the colorant. The pigment derivative is a compound in which a substituent has been introduced into the skeleton of a pigment, and the content of the pigment derivative is preferably 0.01 to 10 mass%, more preferably 0.05 to 6 mass%, and even more preferably 0.1 to 4 mass%, based on the mass of the colorant. When it is 0.01 mass% or more, it is possible to provide excellent releasability from the plastic substrate, and when it is 10 mass% or less, it is possible to suppress reattachment of the printed layer. The resin-type dispersant functions to adsorb to the colorant and stabilize the dispersion in the printing ink, etc., and can be appropriately selected from known resin-type dispersants. The content of the resin-type dispersant is preferably 0.01 to 30 mass%, more preferably 0.05 to 20 mass%, and even more preferably 0.1 to 10 mass%, based on the mass of the colorant. When it is 0.01 mass% or more, the releasability of the plastic substrate is excellent, and when it is 30 mass% or less, the water resistance of the printed layer is excellent.

[0089] The print layer may contain a resin other than the water-soluble resin or the compound containing an acidic group. Examples of such resins include fibrous materials such as nitrocellulose and cellulose acetate propionate, chlorinated polypropylene, vinyl chloride-vinyl acetate copolymer, polyester, acrylic, urethane resin and acrylic urethane, polyamide, polybutyral, cyclized rubber, and chlorinated rubber. These resins may be used alone or in combination of two or more.

[0090] The thickness of the printing layer is preferably 0.1 μm or more and 100 μm or less, more preferably 0.1 μm or more and 10 μm or less, and even more preferably 1 μm or more and 5 μm or less.

[0091] [Adhesive layer] When the release layer is an adhesive layer, the adhesive layer is disposed in contact with the plastic substrate, contains a compound having an acidic group, and plays a role in releasing the plastic substrate by dissolution with a release liquid, peeling, etc. When the adhesive layer contains a resin having an acidic group or a low molecular weight compound having an acidic group, the adhesive layer can be released using the above-mentioned basic aqueous solution. For the compound having an acidic group, the resin having an acidic group, and the low molecular weight compound having an acidic group, the description of (Compound having an acidic group) in the above section [Primer layer] can be applied. The method for forming the adhesive layer is not limited, and the adhesive layer can be formed by using a known method.

[0092] From the viewpoint of releasability, the adhesive layer may be a cured product of an adhesive containing a polyester polyol having an acidic group and at least one polyisocyanate selected from the group consisting of an aliphatic polyisocyanate and an araliphatic polyisocyanate. The cured product corresponds to a resin having an acidic group. The adhesive layer may also be a cured product of an adhesive containing a polyester polyol, at least one polyisocyanate selected from the group consisting of aliphatic polyisocyanates and araliphatic polyisocyanates, and a low molecular weight compound having an acidic group.

[0093] (Polyester polyol) The polyester polyol may have an acidic group and may be appropriately selected from known polyester polyols. By including such a polyester polyol, when a basic aqueous solution is used as the release liquid, the release property is improved by having an ester bond with high affinity with a basic compound, which is preferable. The polyester polyol may be used alone or in combination of two or more kinds.

[0094] The polyester polyol is not particularly limited, but polyester polyols obtained by reacting a carboxyl group component with a hydroxyl group component; or polyester polyols obtained by ring-opening polymerization of lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone) are preferably used. Examples of the carboxyl group component include dibasic acids such as terephthalic acid, isophthalic acid, naphthalenedicarboxylic acid, phthalic anhydride, adipic acid, azelaic acid, sebacic acid, succinic acid, glutaric acid, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, maleic anhydride, and itaconic anhydride, or dialkyl esters thereof, or mixtures thereof. Examples of the hydroxyl group component include diols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, butylene glycol, neopentyl glycol, trimethylolpropane, glycerin, 1,6-hexanediol, 1,4-butanediol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol, 3,3'-dimethylolheptane, 1,9-nonanediol, polyoxyethylene glycol, polyoxypropylene glycol, polytetramethylene ether glycol, polyether polyol, polycarbonate polyol, polyolefin polyol, acrylic polyol, polyurethane polyol, and mixtures thereof. The above carboxyl group components and hydroxyl group components may be used in combination of two or more kinds.

[0095] The polyester polyol may be a polyester urethane polyol obtained by reacting a hydroxyl group in a polyol with a polyisocyanate. The polyester polyol has a urethane bond, and thus exhibits excellent heat resistance and adhesiveness. Examples of the polyisocyanate include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, xylylene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, hexamethylene diisocyanate, and hydrogenated diphenylmethane diisocyanate.

[0096] The polyester polyol may be an acid anhydride-modified product obtained by reacting an acid anhydride with a hydroxyl group in the polyol, thereby introducing a carboxyl group, which is an acidic group, into the polyester polyol. Examples of the acid anhydride include pyromellitic anhydride, mellitic anhydride, trimellitic anhydride, and trimellitic ester anhydride. Examples of the trimellitic ester anhydride include ethylene glycol bisanhydrotrimellitate and propylene glycol bisanhydrotrimellitate.

[0097] The acid value of the polyester polyol is preferably 5.0 mgKOH / g or more, more preferably 10.0 mgKOH / g or more. The acid value of the polyester polyol is preferably 100 mgKOH / g or less, more preferably 80 mgKOH / g or less. When the acid value of the polyester polyol is in the above range, when the polyester polyol is contacted with a release liquid that is a basic aqueous solution, the basic aqueous solution penetrates and decomposes the polyester polyol, thereby exhibiting better release properties. When the adhesive contains a plurality of polyester polyols, the acid value of the entire polyester polyols can be determined from the acid value of each polyester polyol and its mass ratio.

[0098] The number average molecular weight (Mn) of the polyester polyol is preferably 3,000 to 25,000, more preferably 5,000 to 20,000, and particularly preferably 7,000 to 15,000. When the number average molecular weight of the polyester polyol is 3,000 or more, not only the coatability but also sufficient retort resistance can be exhibited, and when it is 20,000 or less, not only the coatability but also the release property is improved, so this is preferable.

[0099] In order to satisfy various physical properties required for the packaging material, the polyester polyol component may contain a combination of multiple polyester polyol components, for example, a polyester polyol having a number average molecular weight of 5,000 to 20,000, and further, in order to improve adhesion to the substrate, a polyester polyol having a number average molecular weight of less than 3,000 may be contained. The content of the polyester polyol having a number average molecular weight of less than 3,000 is preferably 0 to 30 mass %, more preferably 0 to 20 mass %, based on the total mass of the polyester polyol. When it is 30 mass % or less, retort resistance can be maintained.

[0100] (Other polyols) The adhesive constituting the adhesive layer may contain a polyol other than the polyester polyol. The polyol that may be contained other than the polyester polyol is not particularly limited, and examples thereof include polycarbonate polyol, polycaprolactone polyol, polyether polyol, polyolefin polyol, acrylic polyol, silicone polyol, castor oil-based polyol, and fluorine-based polyol.

[0101] (Polyisocyanate) The polyisocyanate to be combined with the above-mentioned polyester polyol to form the adhesive layer is preferably at least one selected from the group consisting of known aliphatic polyisocyanates and araliphatic polyisocyanates.

[0102] Examples of the aliphatic polyisocyanate include acyclic aliphatic diisocyanates such as trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, 1,2-propylene diisocyanate, and 1,2-butylene diisocyanate; alicyclic diisocyanates such as 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, and 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (hereinafter, referred to as isophorone diisocyanate); and polyisocyanates such as allophanate type, nurate type, biuret type, and adduct type derivatives derived from the above diisocyanates, or complexes thereof. The derivative is preferably a nurate type or an adduct type, more preferably an adduct type. As the aliphatic polyisocyanate, a polyisocyanate derived from hexamethylene diisocyanate (hereinafter also referred to as HDI) is preferred, which can easily ensure a balance between releasability and laminate properties.

[0103] Examples of the araliphatic polyisocyanate include araliphatic diisocyanates such as 1,3- or 1,4-xylylene diisocyanate or a mixture thereof, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,3- or 1,4-bis(1-isocyanato-1-methylethyl)benzene or a mixture thereof; and polyisocyanates such as allophanate type, nurate type, biuret type, and adduct type derivatives derived from the above araliphatic diisocyanates, or complexes thereof.

[0104] (Other polyisocyanates) The adhesive may contain polyisocyanates other than the aliphatic polyisocyanates and aromatic aliphatic polyisocyanates, as long as the effects of the present invention are not impaired. Examples of such polyisocyanates include aromatic diisocyanates such as toluene diisocyanate and diphenylmethane diisocyanate; and polyisocyanates such as derivatives of the above diisocyanates or complexes thereof.

[0105] The polyol and polyisocyanate may be mixed so that the molar ratio (NCO / OH) of the isocyanate groups of the polyisocyanate to the hydroxyl groups of the polyol is 0.3 to 10.0, preferably 0.3 to 7.0, and more preferably 0.5 to 5.0.

[0106] (Other ingredients) The adhesive layer may contain, in addition to a silane coupling agent, a phosphorus oxygen acid or a derivative thereof, a leveling agent, an antifoaming agent, and a reaction accelerator, inorganic fillers (e.g., silica, alumina, mica, talc, aluminum flakes, glass flakes), layered inorganic compounds, stabilizers (e.g., antioxidants, heat stabilizers, UV absorbers, hydrolysis inhibitors), rust inhibitors, thickeners, plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, fillers, crystal nucleating agents, catalysts for adjusting the curing reaction, and the like.

[0107] <First substrate, second substrate, plastic substrate> The first substrate used in the present invention is preferably a plastic substrate. In the present invention, the laminate may contain a substrate other than the first substrate, and the substrate other than the first substrate may not necessarily be the target of separation and recovery. In addition, when the second substrate is present, if the second substrate is also to be recovered, it is preferable that the second substrate is a plastic substrate. When there is no need to separate the recovered first substrate from the recovered second substrate, or when the recovered first substrate and the recovered second substrate can be separated after recovery, the first substrate and the second substrate can be separated by performing steps 1 and 2 on the laminate only once. It can be easily separated and recovered. Examples of the plastic substrate include polyolefin resin, polyester resin, polyamide resin, polystyrene resin, vinyl chloride resin, vinyl acetate resin, ABS resin, acrylic resin, acetal resin, polycarbonate resin, polyvinyl alcohol resin, and cellulose-based plastics.

[0108] <Polyolefin base material> From the viewpoint of reuse as a recycled substrate, the plastic substrate is preferably a polyolefin substrate containing a polyolefin resin. Examples of substrates containing such polyolefin resin include plastic substrates such as polyethylene (PE) and biaxially oriented polypropylene (OPP), as well as sealant substrates such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), acid-modified polyethylene, non-oriented polypropylene (CPP), acid-modified polypropylene, and copolymer polypropylene.

[0109] The thickness of the plastic substrate layer is not particularly limited and may be appropriately selected depending on the application. It is preferably 5 to 200 μm, more preferably 10 to 150 μm. In addition, examples of the gas barrier substrate include aluminum foil, a metal vapor deposition layer such as aluminum, and a metal oxide vapor deposition layer such as silica or alumina. The thickness of the aluminum foil is often used in the range of 3 to 50 μm from an economical point of view. In addition, the aluminum foil, the aluminum vapor deposition layer, and the alumina vapor deposition layer dissolve and are released in a basic aqueous solution, so they function as a release layer and can separate adjacent polyolefin resins. The first substrate and the second substrate may each independently be a single layer or a substrate having two or more layers. When a substrate having two or more layers is separated and recovered, it is not necessary that all layers constituting the substrate are separated as long as the expected amount of the detachment layer is detached.

[0110] <Laminated body configuration> Examples of the laminate structure of the present invention are given below, but the laminate structure is not limited thereto. In the following structures, the "substrate layer" does not have to be a single layer, and may be a laminate in which multiple substrates are laminated. Plastic substrate layer (first substrate) / printed layer (first release layer) Plastic substrate layer (first substrate) / Primer layer (first release layer) / Printed layer · Plastic substrate layer (first substrate) / Printing layer (first release layer) / Adhesive layer (second release layer) / Plastic substrate layer (second substrate) · Plastic substrate layer (first substrate) / primer layer (first release layer) / printing layer / adhesive layer (second release layer) / plastic substrate layer (second substrate) · Substrate layer / printed layer / adhesive layer (first release layer) / plastic substrate layer (first substrate) · Base material layer (first base material) / Printing layer (first release layer) / Adhesive layer / Base material layer · Base material layer (first base material) / Printing layer (first release layer) / Base material layer / Adhesive layer (second release layer) / Plastic base material layer (second base material) · Plastic substrate layer (first substrate) / primer layer (first release layer) / printing layer / adhesive layer / vapor deposition layer (second release layer) / plastic substrate layer (second substrate)

[0111] <Manufacturing method of plastic substrate> The plastic substrate can be manufactured using the above-mentioned separation and recovery method. The plastic substrate may be a substrate that has been fragmented by crushing, cutting, pulverization, or the like. The method for manufacturing a plastic substrate includes, for example, preparing a laminate that includes at least a plastic substrate layer and a detachment layer in contact with the plastic substrate layer, the detachment layer being a layer that contains a water-soluble resin or a compound having an acidic group, and recovering the plastic substrate by the above-mentioned separation and recovery method.

[0112] <Method of manufacturing molding material> A molding material can be produced by melt-kneading the plastic substrate recovered by the above-mentioned separation and recovery method. The method for producing a molding material, which is an embodiment of the present invention, preferably includes the following steps 3 to 5. Alternatively, the above-mentioned method for separating and recovering a laminate or the method for producing a plastic substrate may include at least the following step 3, and the method for producing a molding material may include at least the following step 5. When the molding material includes a master batch, it may further include the following step 6. (Step 3) A step of crushing the laminate and immersing the laminate in a release liquid to remove the plastic substrate from the laminate, or a step of crushing the laminate and immersing the laminate in a release liquid to remove the release layer from the laminate. (Step 4) A step of washing the plastic substrate obtained in step 3 with water. (Step 5) A step of melt-kneading the plastic base material obtained in step 4 to obtain recycled resin. (Step 6) A step of mixing the master batch with the recycled resin obtained in step 5.

[0113] The method for crushing the packaging material in step 3 is not particularly limited, and examples thereof include methods using a jaw crusher, impact crusher, cutter mill, stamp mill, ring mill, roller mill, jet mill, and hammer mill. Step 4 may further include a drying step, if necessary. By step 2, a recycled substrate (also called a recycled plastic substrate) can be obtained.

[0114] The melt-kneading step in step 5 refers to adding various additives as necessary, mixing with a Henschel mixer, tumbler, disperser, etc., and then mixing and dispersing using a batch mixer such as a kneader, roll mill, super mixer, Henschel mixer, Shugi mixer, vertical granulator, high-speed mixer, Farmatrix, ball mill, steel mill, sand mill, vibration mill, attritor, or Banbury mixer, a twin-screw extruder, a single-screw extruder, or a rotor-type twin-screw kneader. This results in a recycled resin, which is a resin composition. The shape of the recycled resin is not particularly limited, and may be pellet-shaped, powder-shaped, granular, or bead-shaped. The melt-kneading step is preferably performed using a twin-screw extruder.

[0115] [Master batch] The molding material in the embodiment of the present invention may further contain a masterbatch. The masterbatch is not particularly limited as long as it has compatibility with the recycled resin, and generally, a mixture of a thermoplastic resin such as a polyethylene resin or a polypropylene resin and a colorant can be used. The thermoplastic resin contained in the masterbatch may be used alone or in combination of two or more kinds. The master batch in an embodiment of the present invention may contain a metal soap of an alkali metal, an alkaline earth metal, or zinc, hydrotalcite, a nonionic surfactant, a cationic surfactant, an anionic surfactant, an amphoteric surfactant, an antistatic agent, a flame retardant such as a halogen-based, phosphorus-based, or metal oxide, a lubricant such as ethylene bis alkyl amide, an antioxidant, an ultraviolet absorber, or a filler, as long as the effects of the present invention are not impaired.

[0116] <Method of manufacturing molded body> The molding material obtained by the above-mentioned production method can be heated and molded to obtain a molded article. The heating and molding method is not particularly limited, and examples thereof include injection molding, extrusion molding, blow molding, and compression molding. Molding materials produced using plastic substrates recovered by the separation and recovery method according to an embodiment of the present invention are of high quality because the printing layer and adhesive layer are detached and reattachment of the detached components is suppressed, and the molding materials can be used in a variety of fields, such as home appliances, stationery, automobile parts, toys, sporting goods, medical use, and building and construction materials. EXAMPLES

[0117] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the present invention, parts and % represent parts by mass and % by mass unless otherwise noted.

[0118] <Molecular weight and molecular weight distribution> The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) were measured by GPC (gel permeation chromatography) and calculated as molecular weights using polystyrene as a standard substance. The measurement conditions are shown below. GPC equipment: Showa Denko Shodex GPC-104 Columns: The following columns were used in series connection: Showa Denko Shodex LF-404 x 2 Showa Denko Shodex LF-G Detector: RI (differential refractometer) Measurement conditions: Column temperature 40℃ Eluent: Tetrahydrofuran Flow rate: 0.3mL / min

[0119] <Acid value, hydroxyl value> The acid value and the hydroxyl value were measured according to the method described in JIS K 0070 (1992).

[0120] <Production of Resin for Primer Composition> [Synthesis Example 1-1] (Polyurethane Resin P1) In a reactor equipped with a reflux condenser, a dropping funnel, a gas inlet tube, a stirrer, and a thermometer, while introducing nitrogen gas, 135.7 parts of PPA (a polyester polyol composed of a polycondensation product of propylene glycol and adipic acid and having a number average molecular weight of 2,000), 13.6 parts of PPG (a polyether polyol composed of polypropylene glycol and having a number average molecular weight of 2,000), 28.3 parts of DMPA (2,2-dimethylolpropanoic acid), 105.7 parts of IPDI (isophorone diisocyanate), and 200 parts of NPAC (normal propyl acetate) were charged and reacted at 90°C for 5 hours to obtain a urethane prepolymer solution having an isocyanate group at the end. Next, a mixture of 16.7 parts of AEA (2-(2-aminoethylamino)ethanol) and 350 parts of IPA (isopropyl alcohol) was added dropwise at room temperature over 60 minutes, and then reacted at 70°C for 3 hours to obtain a polyurethane resin solution. NPAC was added to the resulting polyurethane resin solution to adjust the solid content, thereby obtaining a solution of polyurethane resin P1 having a solid content concentration of 30%, a weight average molecular weight of 30,000, Mw / Mn=3.0 and an acid value of 39.3 mgKOH / g.

[0121] <Composition for forming primer layer (primer composition)> [Production Example 1-1] (Primer composition S1) 87 parts of polyurethane resin P1 solution, 5 parts of EA, 5 parts of IPA, and 3 parts of silica particles (P-73 manufactured by Mizusawa Chemicals: hydrophilic silica particles having an average particle size of 3.8 μm) were mixed and stirred using a disper to obtain a primer composition S1.

[0122] <Production of polyols used in adhesives> [Synthesis Example 2-1] (Polyester polyol B1) In a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube, 124 parts of ethylene glycol, 212 parts of neopentyl glycol, 368 parts of 1,6-hexanediol, 645 parts of isophthalic acid, 36 parts of adipic acid and 265 parts of sebacic acid were charged, and the mixture was heated to 250°C while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. Then, 35 parts of isophorone diisocyanate was gradually added, and the reaction was carried out at 150°C for about 2 hours to obtain a polyester polyurethane polyol. 12.0 parts of ethylene glycol bis-anhydrotrimellitate were added to 100 parts of this polyester polyurethane polyol and reacted at 180°C for approximately 2 hours. The mixture was then diluted with ethyl acetate until the solids concentration reached 50%, yielding a solution of partially acid-modified polyester polyol B1 with a number average molecular weight of 9,000 and an acid value of 30.3 mgKOH / g.

[0123] [Synthesis Example 2-2] (Polyester polyol B2) A reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, a dropping tank and a nitrogen gas inlet tube was charged with 58 parts of ethylene glycol, 412 parts of diethylene glycol, 343 parts of neopentyl glycol, 517 parts of isophthalic acid and 393 parts of adipic acid, and the mixture was heated to 250 ° C. while stirring under a nitrogen stream to carry out an esterification reaction. After a predetermined amount of water was distilled and the reaction was continued until the acid value was 5 or less, the pressure was gradually reduced and a deglycolization reaction was carried out at 1 mmHg or less for 5 hours to obtain a polyester polyol. 4.0 parts of trimellitic anhydride were added to 100 parts of this polyester polyol, and the mixture was reacted at 180 ° C. for about 2 hours, and then diluted with ethyl acetate until the solid content concentration was 50%, to obtain a solution of partially acid-modified polyester polyol B2 with a number average molecular weight of 2,000 and an acid value of 23.5 mgKOH / g.

[0124] <Preparation of polyisocyanate solution> [Preparation Example 1] (Polyisocyanate C1) Coronate 2785 (biuret type polyisocyanate derived from hexamethylene diisocyanate, manufactured by Tosoh Corporation) was diluted with ethyl acetate to adjust the solid concentration to 50% and NCO% to 9.6%, to obtain a solution of polyisocyanate C1.

[0125] <Adhesive manufacturing> [Manufacturing Example 2-1] (Adhesive D1) 90 parts of polyester polyol B1 solution, 10 parts of polyester polyol B2 solution, and 8 parts of polyisocyanate C1 solution were mixed, and EA (ethyl acetate) was added to prepare an adhesive solution with a solids concentration of 30%.

[0126] <Manufacture of Laminate> The manufacturing method of the laminate is described below. The primer composition and the printing ink were each diluted with a mixed solvent of EA / IPA (mass ratio 70 / 30) to a viscosity of 15 seconds (25°C, Zahn cup #3 (manufactured by Rigo Co., Ltd.) before use. The thickness of the primer layer and the printing layer were each adjusted to about 1.5 μm.

[0127] [Manufacturing Example 3-1] (Laminate L1) A diluted primer composition S1 and a printing ink R1 (general-purpose laminating ink "LP Bio SX R39 Indigo" manufactured by Toyo Ink Co., Ltd.) were printed in that order onto an OPP (corona-treated stretched polypropylene film, thickness 20 μm) using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and then dried at 50° C. to obtain a laminate having a configuration of OPP / S1 / R1. Next, adhesive D1 was applied to the printed layer of the obtained laminate using a dry laminator in an amount of 2 g / m2 after drying. 2 After coating and drying so that the film was in the above-mentioned order, it was laminated with a CPP (unstretched polypropylene film, thickness 50 μm) to obtain a laminate L1 having a structure of first base layer (OPP) / primer layer (S1) / printed layer (R1) / adhesive layer (D1) / second base layer (CPP).

[0128] [Manufacturing Example 3-2] (Laminate L2) The diluted printing ink R1 was printed onto NY (stretched nylon film, thickness 15 μm) using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50° C. to obtain a laminate having a configuration of NY / R1. Next, adhesive D1 was applied to an LLDPE (unstretched linear low-density polyethylene film, thickness 130 μm) using a dry laminator until the coating amount was 2 g / m 2 After applying and drying so that the resulting laminate had a structure of first base layer (LLDPE) / adhesive layer (D1) / printed layer (R1) / second base layer (NY), the resulting laminate L2 was obtained.

[0129] [Manufacturing Example 3-3] (Laminate L3) The diluted primer composition S1 and printing ink R1 were printed in that order onto the OPP using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and then dried at 50°C to obtain a laminate L3 having a structure of first base layer (OPP) / primer layer (S1) / printing layer (R1).

[0130] [Manufacturing Example 3-4] (Laminate L4) Diluted printing ink R2 (Toyo Ink's general-purpose surface printing ink "Real NEX BO S3 R39 Indigo") was printed onto anti-fog OPP (anti-fog treated stretched polypropylene film, thickness 20 μm) using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50°C to obtain a laminate L4 having a configuration of a first base layer (anti-fog OPP) / printing layer (R2).

[0131] [Manufacturing Example 3-5] (Laminate L5) The diluted printing ink R1 was printed onto PET (polyethylene terephthalate film, thickness 12 μm) using a gravure printing machine equipped with a gravure plate with a plate depth of 30 μm, and dried at 50°C to obtain a laminate L5 having a configuration of a first substrate layer (PET) / printing layer (R1).

[0132] <Manufacture of deinking treatment liquid (deinking liquid)> [Production Example 4-1] (eluent A1) 0.2 parts of polyoxyethylene lauryl ether (POE addition number: 4, HLB: 9.7) as surfactant A, 0.02 parts of BYK-1650 (manufactured by BYK Japan, silicone-based emulsion type defoamer, solid content concentration 27.5%) as defoamer, 2 parts of sodium hydroxide, and 97.8 parts of water were mixed and stirred with a disperser to obtain a release liquid A1.

[0133] [Production Examples 4-2 to 4-5] (Elution Solutions A2 to A5) Elimination solutions A2 to A5 were obtained in the same manner as in Production Example 4-1, except that the blending compositions were changed to those shown in Table 1.

[0134] [Table 1]

[0135] The abbreviations in Table 1 are shown below. Surfactant A: Nonionic surfactant, polyoxyethylene lauryl ether (POE addition number: 4, HLB: 9.7) Surfactant B: Nonionic surfactant, polyoxyethylene acetylene diol (POE addition number: 30, HLB: 17) Surfactant C: Anionic surfactant, POE lauryl ether phosphate (POE addition number: 4, HLB: 10.0) Defoamer: BYK-1650: BYK Japan, silicone emulsion type, solids concentration 27.5%, main solvent: water

[0136] <Separation and recovery of laminated body (deinking test)> [Example 1] (Process 1) A 1000 mL stainless steel beaker equipped with a stirring blade was charged with 800 g of release liquid A1 and 160 g of a sample (fluff) cut from packaging material L1 to a size of 1 cm x 1 cm, and allowed to stand at 70°C, the immersion time shown in Table 2, and 0 rpm. (Process 2) The fluff from step 1 was removed, and 500 g of another release liquid A1 and 20 g of the fluff removed in step 1 were placed in another 1000 mL stainless steel beaker equipped with a stirring blade, and stirred at 70° C. for the stirring time and at 3000 rpm as shown in Table 2. The state of separation and recovery of the laminate was evaluated as follows.

[0137] [Examples 2 to 16, Comparative Examples 1 to 5] The separation and recovery state of the laminate was evaluated in the same manner as in Example 1, except that the materials shown in Table 2 were used. The results are shown in Table 2.

[0138] <Evaluation of the laminate> (Productivity) The time required to process 1000 kg of fluff was calculated using the following formula and evaluated according to the following criteria. (Formula) Productivity (total time required to process 1000 kg of fluff) = (1000 / amount of fluff processed in process 1 (g)) x time required for process 1 (h) + (1000 / amount of fluff processed in process 2 (g)) x time required for process 2 (h) A (Excellent): Productivity is less than 10 hours B (Good): Productivity is 10 hours or more but less than 15 hours C (Acceptable): Productivity is 15 hours or more but less than 20 hours D (Not acceptable): Productivity is 20 hours or more

[0139] (Releasability) The fluff was collected after completion of steps 1 and 2, washed with water, and dried. From the obtained substrates, 10 sheets of the first substrate were sampled, and the removal rate of the printed layer was visually confirmed and evaluated according to the following criteria. A (Excellent): 100% of the printed layer peels off. B (Good): 95% or more but less than 100% of the printed layer peels off. C (Acceptable): Between 90% and 95% of the printed layer peels off. D (Fail): Less than 90% of the printed layer does not peel off.

[0140] (Reattachment (coloring of fluff)) The fluff after the steps 1 and 2 were collected, washed with water and dried. From the obtained substrate, 10 sheets of the first substrate were sampled, and the 10 obtained substrates were stacked and measured for color value L using a spectrophotometer (X-rite eXact, manufactured by X-rite). * x , a * x , b * x was measured. On the other hand, for the substrate before printing, 10 substrates were stacked in the same way and the color value L * y , a * y , b * y was measured. The color difference ΔE was calculated using the following formula, and the re-adhesion was evaluated according to the following criteria. (Formula)ΔE=((L * x -L * y ) 2 +(a * x -a * y ) 2 +(b * x -b * y ) 2 ) 1 / 2 A (Excellent): ΔE is less than 2 B (Good): ΔE is 2 or more and less than 5 C (Acceptable): ΔE is 5 or more and less than 8 D (unacceptable): ΔE is 8 or more

[0141] (Evaluation of recycled materials, manufacturing of recycled films, and transmittance evaluation) The substrate detached through steps 1 and 2 was recovered, washed with water, and dried. The recovered substrate was then extruded at 200°C using a single-screw extruder and pelletized to obtain pellets of recycled resin. The recycled resin was extruded at 200°C using a T-die film molding machine to produce a recycled film with a thickness of 30 μm. In Example 2, only the LLDPE that floated up after separation by gravity separation was recovered to produce a recycled film. Regarding the coloration of the recycled film, the total light transmittance was measured using a haze meter (SH7000, manufactured by Nippon Denshi Kogyo Co., Ltd.) and evaluated according to the following criteria. A (Excellent): Total light transmittance is 90% or more B (Good): Total light transmittance is 80% or more but less than 90% C (Acceptable): Total light transmittance is 70% or more but less than 80% D (unacceptable): Total light transmittance is less than 70%

[0142] [Table 2]

[0143] As is clear from a comparison of Example 1 and Comparative Example 2 (the conventional method, without leaving in step 1), even if the same laminate was deinked in the same deinking solution under the same conditions in step 2, a significant improvement was observed in the releasability, reattachment property, and recycled material evaluations by performing step 1. As shown in Comparative Example 1, the releasability, reattachment property, and recycled material evaluations improve by extending the treatment time, but the improvement is not so great compared to Example 1. As shown in Comparative Example 7, when the amount of fluff was increased in the deinking step (step 2), the stirring efficiency decreased significantly, and as a result, the efficiency of deinking from the substrate also decreased significantly, and the adhesion of the removed components to the substrate was also significant. However, in step 1, in which the substrate was immersed in the desorption liquid without stirring, it was possible to treat the same amount of fluff. Therefore, by performing step 1, it became possible to treat large amounts of fluff efficiently and effectively. As shown in Comparative Example 3, when the step 1 was merely left to stand without the stirring step 2, the detachment layer remained on the substrate with almost no detachment, and the detachment properties were not satisfactory. As shown in Comparative Examples 4 and 6, when the desorption liquid in step 2 does not contain a basic compound, the desorption layer swells in step 1, and although deinking is barely possible due to the stirring effect, reattachment is poor and the quality of the recycled material is also unacceptable. As shown in Comparative Example 5, when the release liquid in step 1 did not contain a basic compound, the release layer did not swell in the standing step, and release was not possible with the stirring time in step 2 similar to that in the other Examples.

[0144] The above evaluation results show that, with the method according to an embodiment of the present invention, even when a large amount of packaging material is processed, the printed layer and adhesive layer can be easily detached from the packaging material, and a high-quality recycled base material with little reattachment of the printed layer and adhesive layer can be efficiently obtained, and further, a high-quality molding material with little coloration can be obtained.

Claims

1. A method for separating and recovering a laminate, which separates and recovers a first substrate from a laminate comprising at least a first substrate and a first detachment layer in contact with the first substrate, the method comprising the following steps 1 and 2: (Step 1) A step of leaving the laminate in a state of being immersed in a first release solution containing a basic compound for a certain period of time. (Step 2) A step of agitating the laminate that has been subjected to step 1 in a second release liquid containing a basic compound to release the release layer and recover the first base material.

2. The method for separating and recovering a carbon black according to claim 1 , wherein the first substrate is a polyolefin substrate.

3. The separation and recovery method according to claim 1 , wherein the laminate further comprises a second substrate.

4. The separation and recovery method according to claim 3 , wherein the laminate further comprises a second release layer in contact with the second substrate.

5. The separation and recovery method according to claim 1 , wherein the laminate further comprises a two-component curing adhesive layer containing a polyol component and a polyisocyanate component.

6. 2. The method for separating and recovering waste materials according to claim 1, wherein the laminate is a package.

7. The separation and recovery method according to claim 1 , wherein the first elution liquid and / or the second elution liquid contains water and a surfactant.

8. 2. The method for separation and recovery according to claim 1, wherein the time required for step 2 is 1:1 or less relative to the time required for step 1.

9. A method for producing a molding material, comprising melt-kneading a substrate 1 separated and recovered by the method for separating and recovering a molding material according to any one of claims 1 to 8.

10. A method for producing a molded article, comprising the steps of: hot-molding a molding material produced by the method according to claim 9 .

Citation Information

Patent Citations

  • Transfer material

    JP2014162089A

  • Coating film removal method and coating film removal device

    JP2015077541A

  • Method for recycling plastic film laminate, material for processing recycled plastic using plastic film laminate, and method for manufacturing the same

    JP2023032031A

  • Label, method for separating label, and method for recovering base material from label

    JP2023051155A

  • Deinking methods

    JP7325877B1